Mass outdoor events and the spread of an airborne virus: English football and Covid-19 - Olczak, M.; Reade, J.; Yeo, M. (Covid Economics, 2020)
The rapid spread of the Covid-19 virus meant that by mid-March 2020, the UK government had stopped outdoor sports from being played in England. Since then, football has resumed behind closed doors, and whether fans should be allowed to attend matches is now the subject of much debate. This column examines whether football matches held in England across February and March helped to spread Covid-19. It finds that attendance at matches resulted in an increase in cases and deaths and concludes that extreme caution should be applied to reopening football to spectators and that there should be close monitoring of any gradual re-opening of stadiums.